The physiology of neonatal resuscitation. Issue 2 (April 2018) - Hooper, Stuart B.; Kitchen, Marcus J.; Polglase, Graeme R.; Roehr, Charles C.; te Pas, Arjan B.
Abstract : Purpose of review: As the infant's physiology changes dramatically after birth, modern neonatal resuscitation approaches should detect and be modified in response to these changes. This review describes the changes in respiratory physiology at birth and highlights approaches that can assist these changes. Recent findings: To better target assistance given to infants at birth, the changes in lung physiology have been classified into three phases. The first phase involves lung aeration. As little or no gas exchange can occur, assistance should focus on airway liquid clearance. During the second phase, as airway liquid resides in lung tissue, assistance should focus on minimizing the complications associated with lung edema. The third phase occurs whenever the liquid is cleared from the tissue and respiratory mechanics stabilize. Although more traditional approaches are most effective during this phase, this is not the case for the first two phases. Furthermore, the glottis actively adducts during apnea in newborns and so noninvasive respiratory support requires the infant to be breathing so that the glottis will open. Summary: The respiratory support provided to infants at birth should match the infant's changing physiology during transition, which requires a more sophisticated approach and equipment than current recommendations.